Distribution of price changes and the measure of underlying inflation - Σιώκης Φώτιος Μ. (SPOUDAI Journal of Economics and Business, 2002)
It is widely accepted that the conventional consumer price index may not be the ideal indicator of underlying inflation due to noise included in the index. To remedy this problem several methods have been proposed. Based on statistical and economic criteria we develop alternative inflation measures called trimmed means. The analysis of Greek CPI data reveals that price changes on a monthly basis are widely dispersed, positively skewed, and, consequently, not normally distributed. Further analysis, based on a number of alternative measures of core inflation, concludes that trimmed means provide valuable information about underlying pressures and predict more accurately future inflation. JEL Classification: C82, E31